2014
DOI: 10.1002/qj.2293
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of model nonlinearity and localization on ensemble Kalman smoothing

Abstract: Ensemble-based Kalman smoother algorithms extend ensemble Kalman filters to reduce the estimation error of past model states utilizing observational information from the future. Like the filters they extend, current smoothing algorithms are optimal only for linear models. However, the ensemble methods are typically applied with high-dimensional nonlinear models, which also require the application of localization in the data assimilation. In this paper, the influence of the model nonlinearity and of the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…In Khare et al (2008) the behaviour of an ensemble Kalman smoother was investigated using the Lorenz-96 model (Lorenz, 1996) and a general atmospheric circulation model. Nerger et al (2014) used the Lorenz-96 model and performed twin experiments with a global ocean model. It was found that the results from the Lorenz-96 model were transferable to more complex models and a much larger state dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Khare et al (2008) the behaviour of an ensemble Kalman smoother was investigated using the Lorenz-96 model (Lorenz, 1996) and a general atmospheric circulation model. Nerger et al (2014) used the Lorenz-96 model and performed twin experiments with a global ocean model. It was found that the results from the Lorenz-96 model were transferable to more complex models and a much larger state dimension.…”
Section: Introductionmentioning
confidence: 99%
“…In Section 3, the application of the NETS to the small highly nonlinear Lorenz-96 model is discussed. The results from applying the smoother in the high-dimensional NEMO ocean model are presented and compared to the results obtained from the Local Error Subspace Transform Kalman Smoother (LESTKS, Nerger et al, 2014) in Section 4. Finally, Section 5 draws the conclusions and finishes with an outlook.…”
Section: Introductionmentioning
confidence: 99%
“…Evensen (2003) shows how an ensemble Kalman smoother can be implemented with a minimal computational cost alongside a preexisting EnKF. Moreover, Nerger et al (2014) shows that such an algorithm is efficient for nonlinear models, and that in their test case, optimal localization parameters for the ensemble Kalman smoother coincide with optimal localization parameters for the EnKF.…”
Section: Discussionmentioning
confidence: 92%
“…Evensen (2003) shows how an Ensemble Kalman Smoother can be implemented with a minimal computational cost alongside a preexisting EnKF. Moreover, Nerger et al (2014) shows that such algorithm is efficient for nonlinear models, and 5 that in their test case, optimal localization parameters for the Ensemble Kalman Smoother coincide with optimal localization parameters for the EnKF.…”
mentioning
confidence: 84%